DNA sequence, products, and transcriptional pattern of the genes involved in production of the DNA replication inhibitor microcin B17. - Genilloud, O (1989)
The 3.8-kilobase segment of plasmid DNA that contains the genes required for production of the DNA replication inhibitor microcin B17 was sequenced. The sequence contains four open reading frames which were shown to be translated in vivo by the construction of fusions to lacZ. The location of these open reading frames fits well with the location of the four microcin B17 production genes, mcbABCD, identified previously through genetic complementation. The products of the four genes have been identified, and the observed molecular weights of the proteins agree with those predicted from the nucleotide sequence. The transcription of these genes was studied by using fusions to lacZ and physical mapping of mRNA start sites. Three promoters were identified in this region. The major promoter for all the genes is a growth phase-regulated OmpR-dependent promoter located upstream of mcbA. A second promoter is located within mcbC and is responsible for a low-level basal expression of mcbD. A third promoter, located within mcbD, promotes transcription in the reverse direction starting within mcbD and extending through mcbC. The resulting mRNA appears to be an untranslated antisense transcript that could play a regulatory role in the expression of these genes.